2019
DOI: 10.1111/pirs.12450
|View full text |Cite
|
Sign up to set email alerts
|

Broadband's relationship to rural housing values

Abstract: Using data for remote rural US counties (n = 887) we estimate the impact of broadband Internet access on median housing value. We account for spatial dependencies in the joint determination of investments in broadband access and housing values using a modified spatial three stage least squares (3SLS) estimator. The data support the central hypothesis that remote rural housing values are positively impacted by higher access. Our estimates suggest that there are declining returns to speed availability, with acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 89 publications
2
24
0
Order By: Relevance
“…Although some studies found that broadband was not an important contributor (Jayakar and Park 2013), a majority of research has documented a positive correlation or even a potentially causal relationship between broadband access/adoption and improvements in income and employment (Kolko 2012;Holt and Jamison 2009;Whitacre et al 2014a). Other studies have shown that broadband matters for other areas of life as well, including civic engagement, housing values, and migration (Mossberger et al 2012;Mahasuweerachai et al 2010;Deller and Whitacre 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies found that broadband was not an important contributor (Jayakar and Park 2013), a majority of research has documented a positive correlation or even a potentially causal relationship between broadband access/adoption and improvements in income and employment (Kolko 2012;Holt and Jamison 2009;Whitacre et al 2014a). Other studies have shown that broadband matters for other areas of life as well, including civic engagement, housing values, and migration (Mossberger et al 2012;Mahasuweerachai et al 2010;Deller and Whitacre 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our study expands on this work by using a spatial hedonic framework to examine broadband’s value for an individual house using two distinct counties in a relatively rural state (Oklahoma). This hedonic approach is significantly different in nature to the aggregate county-level work performed by Deller and Whitacre (2019).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Deller and Whitacre (2019) recently address the relationship between fixed terrestrial Internet availability and housing prices for residents in remote rural counties. Using national data on nonmetropolitan counties not adjacent to metropolitan areas and a series of spatial models, they find a positive and statistically significant impact of broadband availability on housing values across five speed categories, specifically for the lower speed thresholds (Deller and Whitacre 2019). At the county level, they show that a 10 percent increase in Internet speeds is associated with an average housing value increase ranging from $230 to $661 (Deller and Whitacre 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of literature focused explicitly on rural broadband has grown dramatically over the past decade. Several papers have found that broadband availability is an important factor for rural business location choices ( Kim & Orazem, 2017 ; Mack, 2014 ), and others have documented its positive impact on rural in-migration rates ( Mahasuweerachai et al, 2010 ) and housing values ( Deller & Whitacre, 2019 ). COVID-19 has brought the rural broadband issue to the forefront of the policy environment for a variety of institutions ( Cullen, 2020 ; Giorgi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%